2016
DOI: 10.4172/2165-7556.1000181
|View full text |Cite
|
Sign up to set email alerts
|

Psycho Physiological and Subjective Responses to Mental Workload Levels during N-Back Task

Abstract: The present study investigated the effects of mental workload levels on psychophysiological and subjective responses during n-Back task. Heart rate, heart rate variability, shoulder muscle activity, EEG and EOG were measured during performing four mental tasks by 32 males. NASA-TLX completed at the end of each mental task. Using NASA-TLX the subjects stated that the task demands of very high mental task were higher than those of low, medium and high mental tasks. By increasing mental workload LF/HF ratio, shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Slightly higher accuracy was expected because the N-back is a more sustained and controlled stressor. Further, the N-back task is well validated at eliciting different levels of mental workload, specifically different levels of working memory, and physiological stress indices [48,78]. In contrast, the VR-ISS was a more complex task involving a variety of stressors including, noise, task load, decreased visibility, and simulated physical threat.…”
Section: Discussionmentioning
confidence: 99%
“…Slightly higher accuracy was expected because the N-back is a more sustained and controlled stressor. Further, the N-back task is well validated at eliciting different levels of mental workload, specifically different levels of working memory, and physiological stress indices [48,78]. In contrast, the VR-ISS was a more complex task involving a variety of stressors including, noise, task load, decreased visibility, and simulated physical threat.…”
Section: Discussionmentioning
confidence: 99%
“…The participant has to respond by using the keyboard when the position of the currently displayed frame is the same as the one previously presented. This type of a workload is comparable to monotonous monitoring tasks where the participant has to maintain his attention at the same level task ("1-back position") [27]. A sample screenshot for position 1-Back task is shown in Figure 2.…”
Section: Figure 1 the Outline Of The Experimental Taskmentioning
confidence: 99%
“…Several studies have demonstrated the ability to classify mental workload associated with various laboratory tasks (e.g. N-back [13], mental arithmetic [14], Sternberg memory [15], auditory oddball target paradigm [16,17], visual search [17], and a laboratory version of air traffic control for vigilance tests [18]), as well as in more realistic task scenarios like flight [1,17,[19][20][21] or driving [1,22] simulation, using EEG signals. Typically in such studies, different levels of mental workload are induced by altering the difficulty of the task being performed or by introducing secondary tasks.…”
Section: Introductionmentioning
confidence: 99%